PERBEDAAN HASIL BELAJAR SISWA MENERAPKAN MODEL PEMBELAJARAN QUANTUM TEACHING DAN PAIKEM - Desy novita Sari, Cita Ayni Putri Silalahi (FKIP UMN ALWASHLIYAH, 2023)
This study aims to determine the differences in student learning outcomes using the Quantum Teaching and Paikem learning models at Harapan Bangsa Private High School. This research is quantitative research. The sample of this study was 46 people consisting of Quantum Teaching class and Paikem class. The analysis used in this study was the average and t test analysis. The average value in the Quantum Teaching class is 81 with a standard deviation of 7.17 and in the Paikem class the average value is 68 with a standard deviation of 6.27 and in the t-test analysis obtained the value (x_1 )=6.87 and S1^2 =51.45 by using t, the value of t_hitung=6,810 and the value of t_tabel=2,000 is obtained by the t distribution data with t_hitung> t_tabel. So Ho is rejected so that the alternative hypothesis Ha is accepted so there are differences in the Quantum Teaching learning model and the Paikem learning model at Harapan Bangsa Private High School.